2018
DOI: 10.1002/adfm.201805727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morphology on Printed Contact Performance in Carbon Nanotube Thin‐Film Transistors

Abstract: Silver nanoparticles (NPs) are the most widely used conductive material throughout the printed electronics space due to their high conductivity and low cost. However, when interfacing with other prominent printed materials, such as semiconducting carbon nanotubes (CNTs) in thin-film transistors (TFTs), silver is suboptimal when compared to more expensive or less conductive materials. Consequently, there would be significant value to improving the interface of printed silver to CNT films. In this work, the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…We next examine the principal performance parameters of flexible CNT TFTs in the context of previously reported CNT TFT design trade-off relation-ships. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Figure 7a-c shows on/off ratios plotted as a function of normalized g m , V th , and parallel-plate field-effect mobility (µ), respectively. It can be clearly seen that the performance of our LM-CNT device exhibit R e t r a c t e d significantly higher transconductance and low-voltage operation while maintaining a large on/off ratio of >10 5 due to the combined high-conductance and flexibility.…”
Section: Flexible and High-performance Lm-cnt Tftsmentioning
confidence: 99%
“…We next examine the principal performance parameters of flexible CNT TFTs in the context of previously reported CNT TFT design trade-off relation-ships. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Figure 7a-c shows on/off ratios plotted as a function of normalized g m , V th , and parallel-plate field-effect mobility (µ), respectively. It can be clearly seen that the performance of our LM-CNT device exhibit R e t r a c t e d significantly higher transconductance and low-voltage operation while maintaining a large on/off ratio of >10 5 due to the combined high-conductance and flexibility.…”
Section: Flexible and High-performance Lm-cnt Tftsmentioning
confidence: 99%
“…The requirement of printed Ag NPs based electrodes is not only low resistance but also good contact with semiconductor and good morphology. Printed Ag NPs based source/drain electrodes have been commonly reported in p-type organic and carbon-nanotube TFT [118,119,120,121,122,123], though the intrinsic work function of Ag is as low as 4.26 eV [124]. It may be due to the formation of Ag 2 O on a surface that is a high-doped degenerate p-type semiconductor with high work function and moderate electric conductivity.…”
Section: Applications Of the Ag Nps Based Inkmentioning
confidence: 99%
“…Metallic Ag NPs undergo undesirable electrical/thermal migration [115,132], which would result in unpredictable degradation of the device performance [115,122]. Hong et al reported high-performance oxide thin-film transistors, by surrounding Ag nanoparticles firmly with oleic acid to suppress the migration of Ag inside adjacent oxide semiconductors.…”
Section: Applications Of the Ag Nps Based Inkmentioning
confidence: 99%
“…Carbon nanotubes have been considered as one of the emerging 1D materials that present high charge carrier mobility, excellent physical and chemical stability, and proper operating temperature . In addition to combining with semiconductors, carbon nanotubes assisted in lightly n‐doped Si transistor can also realize the emulation of synaptic behaviors.…”
Section: Emerging Materials‐based Synaptic Devicesmentioning
confidence: 99%